Developmental dysregulation of excitatory-to-inhibitory GABA-polarity switch may underlie schizophrenia pathology: A monozygotic-twin discordant case analysis in human iPS cell-derived neurons. (November 2021) - Toritsuka, Michihiro; Yoshino, Hiroki; Makinodan, Manabu; Ikawa, Daisuke; Kimoto, Sohei; Yamamuro, Kazuhiko; Okamura, Kazuya; Akamatsu, Wado; Okada, Yohei; Matsumoto, Takuya; Hashimoto, Kazumichi; Ogawa, Yoichi; et al.
Abstract: Schizophrenia is a major psychiatric disorder, but the molecular mechanisms leading to its initiation or progression remain unclear. To elucidate the pathophysiology of schizophrenia, we used an in vitro neuronal cell culture model involving human induced pluripotent stem cells (hiPSCs) derived from a monozygotic-twin discordant schizophrenia pair. The cultured neurons differentiated from hiPSCs were composed of a mixture of glutamatergic excitatory neurons and gamma aminobutyric acid (GABA)ergic inhibitory neurons. In the electrophysiological analysis, a different pattern of spontaneous neuronal activity was observed under the condition without any stimulants. The frequency of spontaneous excitatory post-synaptic currents (sEPSCs) was significantly higher in the hiPSC-derived neurons of the patient with schizophrenia than in the control sibling at day-in-vitro 30. However, the synaptic formation was not different between the patient with schizophrenia and the control sibling during the same culture period. To explain underlying mechanisms of higher excitability of presynaptic cells, we focused on the potassium-chloride co-transporter KCC2, which contributes to excitatory-to-inhibitory GABA polarity switch in developing neurons. We also revealed the altered expression pattern of KCC2 in hiPSC-derived neurons from the patient with schizophrenia, which could contribute to understanding the pathology of schizophrenia in the developing nervous system. Highlights: To elucidate the pathophysiology of schizophrenia, we used hiPSC-derived neurons from a monozygotic-twin discordant schizophrenia pair Excitatory synaptic inputs were increased in neurons of patient with schizophrenia Lowered activity of KCC2 and delayed GABA polarity switch may contribute to this aberrant excitatory synaptic inputs, and these may underlie the E/I imbalance in schizophrenia pathology